2021
DOI: 10.3390/pharmaceutics13081294
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanocarriers for Anti-HIV Therapeutics: A Focus on Physicochemical Properties and Biotechnological Advances

Abstract: Since HIV was first identified, and in a relatively short period of time, AIDS has become one of the most devastating infectious diseases of the 21st century. Classical antiretroviral therapies were a major step forward in disease treatment options, significantly improving the survival rates of HIV-infected individuals. Even though these therapies have greatly improved HIV clinical outcomes, antiretrovirals (ARV) feature biopharmaceutic and pharmacokinetic problems such as poor aqueous solubility, short half-l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 158 publications
0
9
0
Order By: Relevance
“…Furthermore, there is supportive evidence suggesting that the pathogenesis of HIV-associated dementia is likely attributed to indirect effects of HIV infection on the brain, possibly mediated through the actions of macrophages and microglia [42]. Faria et al [43] proposed the utilization of lipid nanocarriers for anti-HIV therapeutics to enhance penetration into HIV reservoir sites and surmount biological barriers such as BBB upon administration. Nanocarriers, when coated with specific surface stabilizers, offer potential utility in achieving elevated drug concentrations in the brain during CNS administration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is supportive evidence suggesting that the pathogenesis of HIV-associated dementia is likely attributed to indirect effects of HIV infection on the brain, possibly mediated through the actions of macrophages and microglia [42]. Faria et al [43] proposed the utilization of lipid nanocarriers for anti-HIV therapeutics to enhance penetration into HIV reservoir sites and surmount biological barriers such as BBB upon administration. Nanocarriers, when coated with specific surface stabilizers, offer potential utility in achieving elevated drug concentrations in the brain during CNS administration.…”
Section: Discussionmentioning
confidence: 99%
“…LNPs belong to the organic nano-system and have hydrophilic parts exposed to the surrounding aqueous solvent as well as hydrophobic parts facing each other to form a supramolecular structure [ 124 ]. LNPs are particularly attractive for biomedical applications, owing to their enhanced lipid-specific biocompatibility.…”
Section: Np Delivery—a Platform Ensuring the Efficacy And Stability O...mentioning
confidence: 99%
“…A study has shown that SLNs improved the pharmacokinetic parameters of the HIV protease inhibitor atazanavir [ 71 ]. A 2021 study discussed the importance of using lipid-based nanocarriers to deliver anti-retroviral drug molecules, as well as the specificity of the drug molecules delivered to the target [ 72 ]. A 2019 study reported the efficacy of acyclovir solid lipid nanoparticles that resulted in the sustained release of acyclovir achieved as a single dose [ 53 ].…”
Section: Miscellaneousmentioning
confidence: 99%